Circular RNA circ-NCOR2 accelerates papillary thyroid cancer progression by sponging miR-516a-5p to upregulate metastasis-associated protein 2 expression. Issue 9 (September 2020) - Luan, Sha; Fu, Peng; Wang, Xinyu; Gao, Yue; Shi, Ke; Guo, Youmin
Objective: Papillary thyroid cancer (PTC) is one of the most prevalent endocrine malignancies and the fifth most common cancer in women. Circular RNAs (circRNAs) have been shown to play vital functions in cancers, but few studies have focused on the functions and mechanism of dysregulated circRNAs in PTC. Methods: Quantitative reverse transcription PCR was used to measure circ-NCOR2 levels in PTC tissues and cell lines. The functions of circ-NCOR2 in PTC were examined by analysis using the cell counting kit-8, clone forming, flow cytometry, and Transwell experiments. Bioinformatic analysis and dual luciferase reporter gene testing were used to identify the mechanisms of circ-NCOR2. Results: Circ-NCOR2 overexpression was observed in PTC tissues and cells. Silenced or overexpressed expression of circ-NCOR2 strikingly attenuated or facilitated, respectively, the growth, migration, and invasion of PTC cells. Mechanistically, miR-615a-5p was identified as the target of circ-NCOR2. Moreover, circ-NCOR2 enhanced the expression of metastasis-associated protein 2 (MTA2) by sponging miR-615a-5p, thereby facilitating PTC cell progression. Conclusions: Taken together, our findings reveal a novel circ-NCOR2/miR-615a-5p/MTA2 axis in PTC, which could become a potential therapeutic target for this disease.